2021
DOI: 10.1094/pdis-12-20-2556-re
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Gene Pyramiding and Rotation to Combat Widespread Soybean Cyst Nematode Virulence

Abstract: Soybean cyst nematode (SCN) is an important pathogen of soybean causing more than $1 billion in yield losses annually in the United States. Planting SCN resistant soybean cultivars is the primary management strategy. Resistance genes derived from the plant introductions (PI) 88788 (rhg1-b) and PI 548402 (Peking; rhg1-a and Rhg4) are the main types of resistance available in commercial cultivars. The PI 88788 rhg1-b resistance allele is found in the majority of SCN resistant cultivars in the north central US. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Thus, the results highlight that a pyramid of the rhg1-a allele with rhg2 offers an advantage against the virulent SCN populations tested. Since rhg1-b is the most widely used resistance allele in more than 95% of resistant soybean cultivars planted in the USA, current efforts have focused on pyramiding of rhg1-b with other resistance loci to enhance resistance to virulent SCN (Brzostowski and Diers 2017 ; Yu and Diers 2017 ; Meinhardt et al 2021 ). Here, we demonstrated that a combination of rhg1-a and rhg2 genes provides resistance against virulent nematode populations and resistance allele pyramid focused on these genes would be an effective strategy for the management of virulent SCN populations.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, the results highlight that a pyramid of the rhg1-a allele with rhg2 offers an advantage against the virulent SCN populations tested. Since rhg1-b is the most widely used resistance allele in more than 95% of resistant soybean cultivars planted in the USA, current efforts have focused on pyramiding of rhg1-b with other resistance loci to enhance resistance to virulent SCN (Brzostowski and Diers 2017 ; Yu and Diers 2017 ; Meinhardt et al 2021 ). Here, we demonstrated that a combination of rhg1-a and rhg2 genes provides resistance against virulent nematode populations and resistance allele pyramid focused on these genes would be an effective strategy for the management of virulent SCN populations.…”
Section: Resultsmentioning
confidence: 99%
“…PI 88788 has been excessively utilized as a resistance source in modern SCN-resistant soybean cultivars due to resistance being derived from a single rhg1-b allele which allows for convenient breeding by introgression of a single resistance locus (Concibido et al 2004 ; Niblack, 2005 ; Mitchum 2016 ; McCarville et al 2017 ). Consequently, the monoculture of PI 88788-resistant soybean cultivars has facilitated the selection of virulent nematode populations that are capable of overcoming this resistance (Niblack et al 2008 ; McCarville et al 2017 ; Howland et al 2018 ; Meinhardt et al 2021 ). A crucial step to a successful SCN management strategy is the use of resistance sources capable of limiting the selection of virulent nematode populations which has often been undermined while breeding for high-yielding SCN-resistant cultivars (Niblack 2005 ; Chen 2020 ; Meinhardt et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations